USE OF INTEGRATED TECHNOLOGIES IN VOCATIONAL EDUCATION - Abdazimov, Shavkat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract: There is discussed in the article importance of ICT and pedagogical technologies implementation in «Food sekuritu and safety eguipment» teaching in higher education institutions. The article clarifies informational communication and pedagogical technologies, integration, integrated education and these meanings.